2014
DOI: 10.1021/ef401363b
|View full text |Cite
|
Sign up to set email alerts
|

Oil Recovery Performance of Immiscible and Miscible CO2 Huff-and-Puff Processes

Abstract: The recovery performance of immiscible and miscible CO2 huff-and-puff processes for enhanced oil recovery (EOR) in a light crude oil sample was experimentally investigated. The minimum miscibility pressure (MMP) of the original light crude oil–CO2 system was determined by means of the vanishing interfacial tension technique and found to be MMP = 9.18 MPa. Then, the solubility of the CO2 in the light crude oil and oil swelling factor due to the CO2 dissolution in the oil phase were determined at T = 30 °C and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 145 publications
(78 citation statements)
references
References 36 publications
1
77
0
Order By: Relevance
“…Afterward, CO 2 solubility in terms of grams of CO 2 in 100 g of crude oil was determined at various temperatures and saturation pressures using Equations (3)- (7): [1,12] m dis ¼ m co2;i À m co2;f ð3Þ…”
Section: Co 2 Solubility Measurement For Two Heavy Oil Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterward, CO 2 solubility in terms of grams of CO 2 in 100 g of crude oil was determined at various temperatures and saturation pressures using Equations (3)- (7): [1,12] m dis ¼ m co2;i À m co2;f ð3Þ…”
Section: Co 2 Solubility Measurement For Two Heavy Oil Samplesmentioning
confidence: 99%
“…Several researchers have investigated the solubility of CO 2 in water and brines as well as CO 2 solubility in oil and the oil swelling factor to understand the key parameters required to design and simulate oil recovery. [1,[7][8][9][10][11][12][13][14] The solubility of CO 2 in the crude oil was calculated for a wide range of pressures and temperatures by Dodds et al [15] and are reconstructed and presented in Figure 1. Other studies showed that CO 2 solubility in crude oil is a function of several thermodynamic parameters, mainly saturation pressure, temperature, and crude oil properties such as viscosity and density.…”
Section: Introductionmentioning
confidence: 99%
“…Injecting CO 2 at or above MMP increases both the uptake of CO 2 in the reservoir and oil production as interfacial force barriers are eliminated and the oil is displaced as a single phase liquid. 13,[15][16][17] Current methods used to measure the MMP of gas and oil include the rising bubble apparatus (RBA), 18 slim-tube test, 19 and vanishing interfacial tension method. 20,21 The RBA method is illustrated in Figure 1e.…”
mentioning
confidence: 99%
“…As a consequence, more oil can be produced and oil recovery can be enhanced by reducing oil viscosity, expanding oil volume, and extracting the light components of crude oil. [18][19][20][21][22][23] Mohammed-Singh et al 24 summarized the cases of CO 2 huff and puff in oil fields over the past two decades. Among above methods, CO 2 huff and puff has attracted more attention as an efficient and important technique.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16][17] Both soaking time and CO 2 injection volume are important operation parameters to improve the performance of CO 2 huff and puff. [18][19][20][21][22][23] Mohammed-Singh et al 24 summarized the cases of CO 2 huff and puff in oil fields over the past two decades. They found that the best soaking time was 2-4 weeks and massive CO 2 injection enhanced the oil recovery of CO 2 huff and puff.…”
Section: Introductionmentioning
confidence: 99%